O Belo Sertão e os dizeres da convivência em certezas ventiladas de cores, sons e poesia: The beautiful sertão and the words of acquaintance in ventilated certainties of colors, sounds and poetry (Revista de História da UEG (REVHIST), 2020)
The objective of this work is to analyze the discursive construction of the Sertão / Semiarid in the statements of the acquaintance present in the cordéis and in the music. The sources analyzed were: the cordéis produced by ASA (Articulation of the Semiarid), in the period 2003-2004; the cordéis produced by INSA (National Semiarid Institute), in the period 2008-2011; and the CD “Belo Sertão: The acquaintance with the Semi-arid by means of songs”, which was launched in 2006. It was found that, in opposition to the drought discourse, the statements of coexistence establish a beautiful sertão. This discursive operation makes the semiarid identifiable from images and texts that accentuate the natural beauty and richness of a space; the strength, intelligence and cultural expression of a people. As a political strategy, it is about establishing a new discursive order to anchor looks and interpretations, to serve as a foundation for what is said about the Semiarid, as well as the recognition of its identity.Keywords: Sertão. Semiarid. Acquaintance. Cordel. Music.